An ionic covalent organic framework for rapid extraction of polar organic acids from environmental waters. Issue 26 (10th June 2021) - Sun, Jing; Xue, Fang; Gao, Cui-Ling; Li, Lei; Jiang, Hai-Long; Zhao, Ru-Song; Lin, Jin-Ming
Abstract : An ionic covalent organic framework (Fe3 O4 @EB-TFB-iCOF) as a polar adsorbent was synthesized and characterized. Abstract : An ionic covalent organic framework (Fe3 O4 @EB-TFB-iCOF) as a polar adsorbent was synthesized and characterized. It was applied in the magnetic solid phase extraction (MSPE) of four polar organic acids, namely, 2-(2, 4, 5-trichlorophenoxy)propionic acid, 2-methyl-4-chlorophenoxy acetic acid, naphthyloxyacetic acid, and naphthylacetic acid. The organic acids were detected by high performance liquid chromatography-ultraviolet analysis (HPLC-UV). A method for the determination of organic acids based on MSPE-HPLC-UV was established. The method shows good linear regression ( R 2 ≥ 0.9950), high precision (1.53–3.80%, n = 6), and low detection limit (0.10–0.49 ng mL −1 ). The recovery rate of environmental water samples ranges from 73.3% to 101.0%. This method provides a possibility for high sensitivity analysis of polar organic acids.